FAKTOR-FAKTOR YANG MEMPENGARUHI KENYAMANAN SEKSUAL PADA AKSEPTOR KB IUD DI RS.BHAYANGKARA - Umi Kalsum; Sarina Ali (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2021)
Objective: Research Objective to know the factors affecting the Sexual Comfort on IUD KB Acceptors in Rs.Bayayangkara Makassar. Method: Research Method: This research is a cross sectional study. The sample of research with the number of 40 respondents by way of sampling random sampling. Data analysis using chi square test for 95% significance level. Discussion: IUD (Intra Uterine Device) is a widely used contraceptive tool in family planning program in Indonesia. Less than 4.5 million KB acceptor use IUD. However, the use of IUD contraceptives is not a perfect tool, so there are still some disadvantages including: spotting bleeding, menometrorargia, vaginal or flour albus, dysmenorrhea infection and sexual comfort. Result: Research Result: The result of statistical test by using chi square of all the factors that influence the known value of P smaller than a, it can be concluded that the Ho intervention group is rejected and Ha accepted. Conclusion: There is correlation between the factors influencing the Sexual Convenience on KB IUD Acceptors Dirs.Bhayangkara Makassar